2019
DOI: 10.1016/j.jss.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Media on Community Consultation in Exception From Informed Consent Clinical Trials

Abstract: Exception from informed consent Emergency researchInformed consent Community consultation a b s t r a c t Background: Exception from informed consent (EFIC) allows clinician scientists to perform much needed emergency research. Obtaining this exception, however, requires many meetings with community groups for consultation, which can make the process timeconsuming and expensive. We aim to determine the impact of using social media in lieu of some community meetings in an effort to obtain an EFIC. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…63 Although some reports are positive and participants satisfied, 64,65 community consultation and public disclosure are also challenging, time consuming, and costly. 66,67 A study 68 reviewed 28 completed and published acute care studies between 1996 and 2018, that used exception from informed consent or waiver of informed consent. 68 Only 359 (0•6%) of 63 947 study enrolments were withdrawn or did not provide consent for continued study participation.…”
Section: Exception From Consentmentioning
confidence: 99%
“…63 Although some reports are positive and participants satisfied, 64,65 community consultation and public disclosure are also challenging, time consuming, and costly. 66,67 A study 68 reviewed 28 completed and published acute care studies between 1996 and 2018, that used exception from informed consent or waiver of informed consent. 68 Only 359 (0•6%) of 63 947 study enrolments were withdrawn or did not provide consent for continued study participation.…”
Section: Exception From Consentmentioning
confidence: 99%
“…We found that while most (81.7%) participants believed community consultation was important, none of the patients or surrogates could recall being informed of PAMPer via community consultation, and none were aware of opt out procedures. Social media has also been reported to be a cost-effective and efficient means of notifying the public [15,24]. Accordingly, social media has become one of the primary avenues for community consultation for EFIC since the PAMPer study [31].…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have examined patients' and surrogates' opinions regarding EFIC procedures and emergency research after they had participated in the clinical trial [23][24][25][26][27][28]. This is the first of these studies involving trial participants with uncontrolled traumatic hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An EFIC was obtained from the Institutional Review Board to randomize patients into the trial during emergency trauma laparotomy. 12 Patients were only included if they or their legally authorized representative consented to further participation. Patients were enrolled at the Red Duke Trauma Institute at Memorial Hermann Hospital-Texas Medical Center, which admits >6000 adult trauma patients per year and is one of two American College of Surgeons verified level 1 trauma centers in Houston, Texas, USA.…”
Section: Methodsmentioning
confidence: 99%